Motivation for running in a half-marathon among university students - Malchrowicz-Mośko, Ewa; Villarreal, Javier; Chlebosz, Karolina; Glapa, Agata (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The purpose of the study was to examine the motivations to participate in a half-marathon among two groups of university students (local university students and sport-tourists university students) and also to evaluate the differences between them. Material and Methods. The sample comprised 178 university students (59% of male and 41% of female) that participated in the 6th Poznan Half Marathon. To evaluate the motivation to participate in the half-marathon event, a selfconstructed questionnaire was used. Results. Results indicated that local university students and sport-tourists university students have similar forms of motivation and similar meanings to the event participation with some significance differences. Conclusions. In general, the findings of the present study provide an understanding of motivation to participate in a half-marathon event in different university student groups. These results might be useful for sport managers to analyze consumer behavior and utilize the results in their everyday practice, especially in the strategic planning, marketing and implementation of massive sport events.
Keywords: motives; half marathon; runners; university students